Effects of lambda-carrageenan on equid herpesvirus 3 in vitro - Vissani, Maria Aldana; Galdo Novo, Sabrina; Ciancia, Marina; Zabal, Osvaldo Alfredo; Thiry, Etienne; Bratanich, Ana Cristina; Barrandeguy, Maria Edith (2017)
The purpose of this study was to evaluate the activity of l-carrageenans on EHV-3 in vitro. Confluent monolayers of EDerm cells were infected with 590 plaque forming units (PFU) of EHV-3 per well, simultaneously, with different concentrations of l-carrageenans in a total volume of 500 ml. After 1 h of incubation at 37C, inoculum was discarded and minimum essential medium supplemented with carboxymethyl cellulose 0.75% was added.